2019
DOI: 10.1038/s41598-019-51675-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated preoperative platelet distribution width predicts poor prognosis in Esophageal Squamous Cell Carcinoma

Abstract: Activated platelets play a multifaceted role in tumorigenesis and progression. Platelet distribution width (PDW) is generally applied platelet parameters from routine blood test. Preoperative PDW has been considered a prognostic factor in many cancers. Nevertheless, the prognostic value of PDW in esophageal squamous cell carcinoma (ESCC) remains unknown. The study aimed to investigate whether preoperative PDW could serve as a prognostic factor in patients with ESCC. A total of 495 patients with ESCC undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
0
15
1
Order By: Relevance
“…The PDW levels at the pretherapeutic, preoperative, and postoperative time points were 11.1 (10.2-12.4) fl, 10.2 (9.1-11.2) fl, and 9.9 (8.9-10.9) fl, respectively, while serum CRP levels at the three time points were 0.13 (0.06-0.51) mg/dl, 0.14 (0.06-0.41) mg/dl, and 0.13 (0.05-0.46) mg/dl, respectively. Interestingly, the PDW levels in our cohort tended to be lower than in earlier studies of esophageal cancer (9,10).…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…The PDW levels at the pretherapeutic, preoperative, and postoperative time points were 11.1 (10.2-12.4) fl, 10.2 (9.1-11.2) fl, and 9.9 (8.9-10.9) fl, respectively, while serum CRP levels at the three time points were 0.13 (0.06-0.51) mg/dl, 0.14 (0.06-0.41) mg/dl, and 0.13 (0.05-0.46) mg/dl, respectively. Interestingly, the PDW levels in our cohort tended to be lower than in earlier studies of esophageal cancer (9,10).…”
Section: Resultscontrasting
confidence: 92%
“…Consequently, the advantage of the CPC score is that it enables detection of EC patients with favorable and poor prognoses, irrespective of ypTNM Stage. Most studies of the association between PDW and malignancies have shown that high PDWs correlate significantly with poor prognoses (8)(9)(10)(11)(12). Within the tumor microenvironment, tumor cells induce platelet activation and aggregation, and enhance thrombopoiesis by releasing thrombopoietic cytokines, such as interleukin-6 (IL-6) and tumor-derived platelet factor 4 (PF4) (7).…”
Section: Discussionmentioning
confidence: 99%
“…believed that PDW < 12.5 could predict the poor prognosis of esophageal cancer, consistent with this study. However, in contrast to Song Q [17] etal., he believed that high PDW could predict the poor prognosis of esophageal cancer. In predicting the prognosis of esophageal cancer, due to inconsistent results, the role of LMR in the prognosis of esophageal cancer was very different.…”
Section: Discussionmentioning
confidence: 77%
“…1 ), we found that MPV and PDW/PCT have the highest potential to be independent prognostic factors of BTC, which was subsequently confirmed by the final multivariable Cox analysis. MPV, representing platelet size, has been demonstrated to be an independent predictor for OS in many cancers, and a high MPV has been reported as a poor indicator of OS in pancreatic cancer [ 11 ], invasive breast cancer [ 12 ], lung cancer [ 13 ] and esophageal carcinoma [ 14 ]. Our findings add to the accumulating evidence that high MPV is an independent negative predictor of OS.…”
Section: Discussionmentioning
confidence: 99%
“…The role of platelets as regulators of inflammation has been recognized, and as a result, the prognostic ability of platelet-related indices has been investigated in many cancers. Platelet count (PLT) and morphologic indices, including the mean platelet volume (MPV), plateletocrit (PCT), and platelet distribution width (PDW), have been frequently studied in a number of cancers, including pancreatic cancer [ 11 ], invasive breast cancer [ 12 ], lung cancer [ 13 ], and esophageal cell carcinoma [ 14 ]. However, the relationship between platelet-related indices and prognosis in BTC remains unknown.…”
Section: Introductionmentioning
confidence: 99%